The Influence of Locus of Control, Social Media, Financial Literacy on Gen-Z Online Investment Decisions - Kumalasari, Lalita Christi; Wijayanto, Edi; Hamida, Nurul (Journal of Applied Management and Business, 2025)
This research aims to analyze the influence of locus of control and social media on online investment decisions with financial literacy as an intervening variable on gen z in the digital era. The design of this study is a causal applied quantitative. The data collection method uses a questionnaire that is distributed randomly and analyzed using SmartPLS 3 software. The sampling technique used is purposive sampling technique and the number of samples is 100 respondents who were students at Politeknik Negeri Semarang. The instrument trial was analyzed using the outer model test and the hypothesis test was analyzed using the inner model test. The results of this study indicate that locus of control, social media and financial literacy have a significant and positive influence on investment decisions. In addition, locus of control and social media influence investment decisions both directly and through financial literacy as an intervening variable.